Assessment of land use change and sedimentation modelling on environmental health in Tropical river - Mohd Ekhwan Toriman (2018)
© 2015, Malaysian Society of Analytical Sciences. All rights reserved. Sediments are defined as the organic and inorganic materials or solid fragments derived from the weathering processes of sand, pebbles, silt, mud and loess. The objective of this research is to forecast sediment volume in the Lam Phra Phloeng reservoir by using the Neuro-genetic Optimizer model to calculate the sediment volume from runoff, rainfall, and sediment volume data. The results from satellite imagery interpretation elucidated that from 2002 to 2005, forest area decreased approximately 50,220 km2or 36%, and was converted to agricultural land. By applying the USLE equation, the soil erosion area was found to increase approximately 185,341 tons/year between 2002 and 2005. This result illustrated that the impact of land use change greatly increased sedimentation volume. In applying the Neuro-genetic Optimizer model, the learning rate and momentum of this model was 0.9 and 0.1, respectively, and the initial weight value was +/-3. The model forecasted the annual sediment volume in the Lam Phra Phloeng reservoir in 2005 to be 49,855 tons with R2equals to 0.9994. The regression model, on the other hand, forecasted the sediment volume using the equation Y=198. 48x 1.1783 with R2equals to 0.9974, and the annual sediment volume was estimated to be 45,346 tons. The actual sediment volume in the reservoir in 2005 was obtained from The Royal Irrigation Department, which was found to be 48,697 tons.